Breaking diffraction limit of lateral resolution in optical coherence tomography - Wang, Benquan; Lu, Rongwen; Zhang, Qiuxiang; Yao, Xincheng (Quantitative Imaging in Medicine and Surgery, 2013)
Quantitative imaging of biomedical specimens is essential in biomedical study and diagnosis. Given excellent capability in three-dimensional (3D) imaging, optical coherence tomography (OCT) has been extensively used in ophthalmic imaging, vascular medicine, dermatological study, etc. Lateral resolution of the OCT is light diffraction limited, which precludes the feasibility of quantitative assessment of individual cells. In this paper, we demonstrated the feasibility of breaking diffraction-limit in OCT imaging through virtually structured detection (VSD). OCT examination of optical resolution target verified resolution doubling in the VSD based OCT imaging. Super-resolution OCT identification of individual frog photoreceptors was demonstrated to verify the potential of resolution enhancement in retinal imaging. We anticipate that further development of the VSD based OCT promises an easy, low cost strategy to achieve sub-cellular resolution tomography of the retina and other biological systems.